Relevance of Sex and Subtype in Patients With IBS: An Exploratory Study of Gene Expression. Issue 1 (January 2020) - Weaver, Kristen R.; Melkus, Gail D'Eramo; Fletcher, Jason; Henderson, Wendy A.
Background: Psychological state, stress level, and gastrointestinal function are intricately related and relevant to symptom exacerbation in patients with irritable bowel syndrome (IBS), but genetic contributors to this brain–gut connection are not fully understood. The purpose of this exploratory study was to compare gene expression in participants with IBS to that of healthy controls (HC) and to examine patterns of expression in participants with IBS by sex and IBS subtype. Method: Participants were recruited to an ongoing protocol at the National Institutes of Health. Differences in demographic and clinical characteristics were assessed using descriptive statistics and Mann–Whitney U tests. Expression levels of 84 genes were evaluated in peripheral whole blood using Custom RT 2 Profiler polymerase chain reaction (PCR) Arrays, and data analysis was performed through GeneGlobe Data Analysis Center. Results: Participants with IBS ( n = 27) reported greater levels of perceived stress ( p = .037) and differed in expression values of ±2 for the genes ADIPOR1, ADIPOR2, CNR2, COMT, OXTR, and PPARA compared to HC ( n = 43). Further analyses by sex and IBS subtype revealed differential patterns of gene expression related to the endocannabinoid system, cytokines, stress, and sex steroid hormones. Conclusions: Diverse yet interconnected processes such as metabolism, inflammation, immunity, social behavior, and pain are associated with differences in gene expression between participants with IBS and HC. These findings lend support for genomic associations with the brain–gut connection in patients with IBS and highlight the relevance of sex and IBS subtype in performing such analyses.